Dietary habits in the context of body composition of young adult females - Sofková, Tereza; Hřivnová, Michaela; Chrásková, Marie (Anthropological Review, 2019)
Appropriate dietary habits and healthy nutrition play a part in weight control. Set positive principles make precondition for satisfactory state of the body and its composition. Body mass index (BMI) is most commonly used to assess optimal body mass in relation to health risks. However, BMI does not enable the representation of individual body components and may lead to misdiagnosis in one person. The aim of our study was to evaluate dietary habits and selected body composition parameters based on BMI. Moreover, we evaluated these parameters in relation to the daily frequency of meals. The research group consisted of 318 female students of pedagogical disciplines of Palacký University in Olomouc, aged between 18 and 30 years. (22.3±2.5 years). The survey was conducted in March 2018 and 2019. Data on dietary habits were acquired through a questionnaire survey that focused on the daily frequency of meals. Multi-frequency bioimpedance analysis using InBody 720 analyser was used to determine body composition parameters. In the normal weight BMI (BMI_N) category, the selected parameters (BFP: body fat percentage, VFA: visceral fat, FFM: fat-free mass) based on general recommendations for body composition are met. In the overweight and obesity (BMI_O) category, the mean BFP values fall, as expected, into the obesity category (≥ 35%). We may conclude that statistically significantly lower relative risk of damage to health assessed by the body fat and visceral fat (BFM, BFP, VFA, BFMI) was found to be significantly lower in women who consume 5 meals per day compared to women who consume 4 or less daily portions of food. The differences between the BMI categories for individual meals during the day were statistically insignificant for the group we investigated. We evaluate the dietary habits positively based on the low frequency of skipping meals.